Naches Trail [large type] - Rundell, B. N. (Rundell, B. N. McCain chronicles, 2024)
"The great Northwest -- land of the Nez Perce, Yakima, Nisqually, and Muckleshoot peoples -- beckoned settlers and the remnants from the gold fields. However, it had been ravaged by the Indian wars of 1855 and the years following. Though the Civil War is now over, not all has been forgotten nor forgiven, and renegades remain committed to making their mark against the Union. It is into this conflict that Elijah McCain's search for his missing sons brings him. This hunt takes him into the scablands, across the desolate plains, and leads him to join a freighter wagon train that will cross the Cascade Mountain Range by way of the Naches Trail, the most treacherous and deadly route known at the time. The journey becomes even more perilous due to an attack on a wagon train, leaving a massacre in its wake. The same renegades now set their sights on a gold-carrying wagon train, unaware of the formidable man they are about to encounter -- former Union Colonel Elijah McCain. This encounter may prove to be their mistake -- or perhaps Elijah's."--